1975
DOI: 10.1002/ijc.2910150209
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐induced angiogenesis: Lack of inhibition by irradiation

Abstract: The effect of irradiation of tumors on their ability to induce vascular responses (angiogenesis) was studied. Rat Walker carcino-sarcoma 256, rabbit V2 carcinoma, mouse (C57B1) melanoma and mouse (129) teratoma (OTT 6050, 100K) were irradiated with up to 5000R, then grafted either to the chicken chorioallantoic membrane or intracorneally into adult rabbits to assess competence to provoke angiogenesis. For all tumors and both assay systems the results were similar: irradiation did not interfere with tumor-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 8 publications
0
22
0
1
Order By: Relevance
“…It is possible that EC proliferation occurs at an earlier point in the development of the mucinous tumour vasculature, that incorporation of ECs from surrounding vessels occurred and that migration of ECs from adjacent regions or remodelling of the existing vasculature contribute to the increased MVD observed in mucinous tumours. Previous studies have demonstrated vascular sprout formation due to EC migration and redistribution in the absence of EC proliferation (Auerbach et al, 1975;Sholley et al, 1984). EC migration is thought to determine the rate of vascular growth and to stimulate EC proliferation (Stokes, 1992).…”
Section: Vegf Mrna Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that EC proliferation occurs at an earlier point in the development of the mucinous tumour vasculature, that incorporation of ECs from surrounding vessels occurred and that migration of ECs from adjacent regions or remodelling of the existing vasculature contribute to the increased MVD observed in mucinous tumours. Previous studies have demonstrated vascular sprout formation due to EC migration and redistribution in the absence of EC proliferation (Auerbach et al, 1975;Sholley et al, 1984). EC migration is thought to determine the rate of vascular growth and to stimulate EC proliferation (Stokes, 1992).…”
Section: Vegf Mrna Expressionmentioning
confidence: 99%
“…EC proliferation during angiogenesis has been observed in a number of studies; however, limited vascular growth can occur without EC proliferation (Auerbach et al, 1975;Sholley et al, 1984). Despite the proposed importance of EC proliferation in angiogenesis and the many observations of increased MVD in tumours, only one (Vermeulen et al, 1995) of the several studies (Fox et al, 1993;Weidner, 1994, 1995) examining EC proliferation in the tumour vasculature demonstrated a correlation between EC proliferation and MVD.…”
mentioning
confidence: 99%
“…100 Although many of the early studies on tumour angiogenesis were carried out using the angiogenic privilege of the cornea as a model system, 101,102 anticancer drugs such as bevacizumab are now proving to be of benefit for the treatment of corneal disease. 103 However, clinical data on safety and efficacy of bevacizumab is currently limited to non-randomised, largely non-comparative case series, and antiangiogenic agents developed and approved specifically for corneal neovascularisation are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, non-angiogenic and angiogenic human tumors have similar proliferation rates. In another study, tumor cells were treated with ionizing irradiation to render them incapable of cell division and were then implanted into the rabbit cornea; these cells still induced angiogenesis similar to nonirradiated tumor cells (Auerbach et al 1975). A third demonstration of the dissociation of tumor cell proliferation and angiogenesis came from experiments with the SV40 large-T oncogene.…”
Section: Dissociation Of the Tumor Cell Proliferative Inducing Functimentioning
confidence: 99%